Simulation of Flapping-wing Unmanned Aerial Vehicle using X-plane and Matlab/Simulink - Kaviyarasu, A.; Kumar, K. Senthil (Defence Science Journal, 2014)
This paper presents the simulation of flapping-wing unmanned aerial vehicle model using X-plane and Matlab/ Simulink. The flapping-wing ornithopter model (i.e. an aircraft that flies by flapping its wings) has been developed in plane maker software and executed in the X-plane environment. The key idea of flapping-wing mechanism in X-plane software is by varying its dihedral angle sinusoidally. This sinusoidally varying dihedral angle of wing creates upward and downward stroke moments inturn this creates a lift and a forward thrust for flying the flapping-wing model. Here pitch, roll, yaw and throttle (flapping rate) is fed as reference input through the user datagram protocol (UDP) port. The difference between the reference inputs, the simulated outputs are again fed back to simulator through UDP port and the gains are observed for the responses of flapping-wing unmanned aerial vehicle in Matlab/Simulink environment. Here various gains are used to monitor the optimized flying of flapping-wing model. Defence Science Journal, Vol. 64, No. 4, July 2014, pp.327-331, DOI:http://dx.doi.org/10.14429/dsj.64.4933